2019
DOI: 10.1093/mnras/stz063
|View full text |Cite
|
Sign up to set email alerts
|

CGM properties in VELA and NIHAO simulations; the OVI ionization mechanism: dependence on redshift, halo mass, and radius

Abstract: We study the components of cool and warm/hot gas in the circumgalactic medium (CGM) of simulated galaxies and address the relative production of OVI by photoionization versus collisional ionization, as a function of halo mass, redshift, and distance from the galaxy halo center. This is done utilizing two different suites of zoom-in hydro-cosmological simulations, VELA (6 halos; z > 1) and NIHAO (18 halos; to z = 0), which provide a broad theoretical basis because they use different codes and physical recipes f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 72 publications
2
27
0
Order By: Relevance
“…The feedback recipe of the NIHAO simulations results in realistic galaxies across more than two orders of magnitude in halo mass (Wang et al 2015) with baryonic properties matching several key observables of local galaxies (e.g. Obreja et al 2016;Macciò et al 2016;Santos-Santos et al 2018;Roca-Fàbrega et al 2019). Here, we extended the mass resolution of the NIHAO sample roughly a magnitude higher in mass resolution and contrasted our model predictions to observational results obtained for the MW and local massive disk galaxies.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…The feedback recipe of the NIHAO simulations results in realistic galaxies across more than two orders of magnitude in halo mass (Wang et al 2015) with baryonic properties matching several key observables of local galaxies (e.g. Obreja et al 2016;Macciò et al 2016;Santos-Santos et al 2018;Roca-Fàbrega et al 2019). Here, we extended the mass resolution of the NIHAO sample roughly a magnitude higher in mass resolution and contrasted our model predictions to observational results obtained for the MW and local massive disk galaxies.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…They used non-equilibrium ionization, and a flickering AGN as an additional ionization source, in zoom simulations otherwise using the EAGLE code and physics. In NIHAO and VELA zoom simulations, Roca-Fàbrega et al (2019) found a roughly equal mix of collisionally and photoionized O vi in z = 0, M 200c = 10 11 -10 12.6 M haloes. Overall, this sup-ports the picture that observed O vi does not have one single origin.…”
Section: Discussion and Comparison To Previous Workmentioning
confidence: 92%
“…A complication with O vi is that the implications of the observations depend on whether the gas is photoionized or collisionally ionized. This is often uncertain from observational data (e.g., Carswell et al 2002;Tripp et al 2008;Werk et al 2014Werk et al , 2016, and simulations find that both are present in the CGM (e.g., Tepper-García et al 2011;Rahmati et al 2016;Oppenheimer et al , 2018Roca-Fàbrega et al 2019). The uncertainty in the ionization mechanism leads to uncertainties in which gas phase is traced, and how much mass is in it.…”
Section: Introductionmentioning
confidence: 99%
“…The only clear distinction between clouds in the highest-mass halos and those about lower-mass galaxies is at column densities log N (H I) 16.0, which are essentially absent in the highest-mass galaxies (log M 11.3). The lack of O VI in these halos (see Paper II) also indicates there is little cool gas at very low densities, log n H −4 (e.g., Stern et al 2018;Roca-Fàbrega et al 2019), which would give rise to photoionized O VI. This may imply gas below some critical density is readily evaporated, heated, and ionized to a point where it is not detected in our H I selection, while the higher density gas can survive.…”
Section: Summary and Concluding Remarksmentioning
confidence: 91%